2020
DOI: 10.1002/tkm2.1244
|View full text |Cite
|
Sign up to set email alerts
|

Eppikajutsuto (a Japanese herbal medicine) regulates mTOR and induces apoptosis in oral cancer cells

Abstract: AimThe effectiveness of Japanese traditional (Kampo) medicine is gradually attracting attention worldwide. It is typically known to be effective against cancer as a supportive therapy, but the antitumor effect of Kampo formulas is not fully established. We therefore evaluated the antitumor effect of eppikajutsuto.MethodsWe evaluated the antitumor effect of eppikajutsuto by cell viability assay, western blotting, and apoptotic cell assay using an oral squamous cell carcinoma cell line OSC‐19.ResultsWe found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Although it is difficult to fully understand the mechanisms of its effects, the results of our study indicate that EKJT downregulated the protein expression of mTOR but did not regulate ERK1/2 and phospho-ERK1/2 in OSC19 expression. We observed that cell proliferation inhibition and apoptosis induction depended on EKJT in vitro [7] . It is possible that EKJT exerts an effect on LM through mTOR suppression.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Although it is difficult to fully understand the mechanisms of its effects, the results of our study indicate that EKJT downregulated the protein expression of mTOR but did not regulate ERK1/2 and phospho-ERK1/2 in OSC19 expression. We observed that cell proliferation inhibition and apoptosis induction depended on EKJT in vitro [7] . It is possible that EKJT exerts an effect on LM through mTOR suppression.…”
Section: Discussionmentioning
confidence: 68%
“…We observed that cell proliferation inhibition and apoptosis induction depended on EKJT in vitro. [ 7 ] It is possible that EKJT exerts an effect on LM through mTOR suppression. In a previous report, alkaloids of Ephedra Herba showed anti-inflammatory effects and CaSO 4 of gypsum elevated aquaporin expression.…”
Section: Discussionmentioning
confidence: 99%
“…reported a 14‐year‐old boy with a central conducting lymphatic anomaly who had chylothorax that was responsive to sirolimus, which is a mechanistic target of rapamycin (mTOR) inhibitor 2 . A recent study reported 3 that TJ‐28 exhibited an antitumor effect against oral squamous cell carcinoma cell in vitro by suppressing mTOR activation. As both TJ‐28 and sirolimus have an inhibitory effect on mTOR, we hypothesized that it might be effective in chylothorax.…”
Section: Figmentioning
confidence: 99%
“…Kampo medicine (traditional Japanese medicine) is a medical system that is rooted in ancient Chinese medicine, which has been systematically adapted to suit the climate, environment, and culture of Japan. The diagnostic approach applied in Kampo medicine has become popular worldwide and the treatment has achieved excellent outcomes for several diseases [ 1 , 2 ]. Recently, coronavirus disease 2019 (COVID-19) has been the center of attention, and many studies have shown that Kampo medicine can reduce the incidence rate and severity of cases [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%